Engaging primary care patients with existing online tools for weight loss: A pilot trial. (23rd February 2022) - McVay, Megan A.; Cooper, Kellie B.; Donahue, Marissa L.; Seoane, Montserrat Carrera; Shah, Nipa R.; Webb, Fern; Perri, Michael; Jake‐Schoffman, Danielle E.
Abstract: Objective: Free online tools show potential for promoting weight loss at a low cost, but there is limited evidence about how to effectively engage patients with them. To address this, a low‐dose, flexible intervention was developed that aims to enhance weight‐related discussions with primary care providers (PCPs) and engage patients with an organic (i.e., not researcher‐created) weight loss‐focused social media community and online self‐monitoring tool. Feasibility and acceptability of the intervention was evaluated in a single‐arm, 12‐week pilot. Methods: PCPs were recruited at two clinics, then PCP's patients with upcoming appointments were identified and recruited. Patients received an interactive online kickoff before their scheduled primary care appointment, then 8 follow‐up messages over 12 weeks via email or their electronic health record patient portal. Patients completed assessments at baseline, post‐appointment, and week 12. Primary care providers and patients completed semi‐structured interviews. Results: All PCPs approached enrolled (n = 6); patient recruitment was on track to meet the study goal prior to COVID‐19 restrictions, and n = 27 patients enrolled. Patient satisfaction with the pre‐appointment kickoff was high. Twenty‐four patients reported discussing weight‐related topics at their primary care appointment and all were satisfied with the discussion. Twenty‐two patients completed 12‐week assessments. Of these, 15 reported engaging with the self‐monitoring tool and 9 with the social media community. Patient interviews revealed reasons for low social media community engagement, including perceived lack of fit. On average, patients with available data (n = 21) lost 2.4 ± 4.1% of baseline weight, and 28.6% of these patients lost ≥3% of baseline weight. Primary care providers reported high intervention satisfaction. Conclusions: The intervention and trial design show potential, although additional strategies are needed to promote tool engagement.